Building a Model on Influence of Behavioural and Cognitive Factors on Personal Financial Planning: A Study Among Indian Households. Issue 4 (August 2019) - Mahapatra, Mousumi Singha; Raveendran, Jayasree; De, Anupam
Abstract: Personal financial planning is an emerging area of interest, given the complexities and risks involved in investments and financial markets. As an extension to studies in the field of cognitive and behavioural decision theories, the role of financial cognition (FC) and mental accounting (MA) is examined as antecedents to personal financial planning (PFP) of Indian households and established as a model to represent the same. The study considers factors, that is, financial attitude (FA), risk attitude (RA) and financial knowledge (FK), to measure FC and uses the components of mental budgeting (MB), current income (CI), current assets (CAs) and future income (FI) to study MA as per the behavioural life cycle hypothesis. The study used a structured questionnaire to explore PFP in all the areas of financial interest, that is, cash flow management (CM), investment (INV), insurance (INSU), retirement (RP), tax (TAX) and estate planning (EP). The salaried individuals from different sectors are considered as samples for the study. The data have been collected from all-India representative samples. The analysis has been done with 359 responses from Indian households. The confirmatory factor analysis (CFA) has been used to establish and validates the measurement model.